2016
DOI: 10.1021/acsmedchemlett.6b00100
|View full text |Cite
|
Sign up to set email alerts
|

Stereochemistry Balances Cell Permeability and Solubility in the Naturally Derived Phepropeptin Cyclic Peptides

Abstract: Cyclic peptide (CP) natural products provide useful model systems for mapping "beyond-Rule-of-5" (bRo5) space. We identified the phepropeptins as natural product CPs with potential cell permeability. Synthesis of the phepropeptins and epimeric analogues revealed much more rapid cellular permeability for the natural stereochemical pattern. Despite being more cell permeable, the natural compounds exhibited similar aqueous solubility as the corresponding epimers, a phenomenon explained by solvent-dependent confor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
60
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(61 citation statements)
references
References 45 publications
0
60
0
Order By: Relevance
“…and previously characterized for their activity as weak proteasome inhibitors (29). It was shown previously that stereo-inversion of the Pro residue to form epiphepropeptin (EpD) significantly altered the compound conformation as determined by nuclear magnetic resonance (NMR) analysis (28). Thus, it is unlikely that the compounds described here as possessing T3SS-inhibitory activity would retain the proteasomal inhibition of the natural product.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…and previously characterized for their activity as weak proteasome inhibitors (29). It was shown previously that stereo-inversion of the Pro residue to form epiphepropeptin (EpD) significantly altered the compound conformation as determined by nuclear magnetic resonance (NMR) analysis (28). Thus, it is unlikely that the compounds described here as possessing T3SS-inhibitory activity would retain the proteasomal inhibition of the natural product.…”
Section: Discussionmentioning
confidence: 83%
“…As part of a previous study (28), a library of 20 synthetic peptides and peptomers based on the structure of a natural product, phepropeptin D (29), were synthesized and placed in an internal screening library. These peptomers were not previously screened for any bioactivity and may have a high intrinsic potential to disrupt protein-protein interactions (30), such as those critical for assembly of a large proteinaceous structure such as the T3SS.…”
Section: Development and Use Of An Nf-b-gfp Stable Cell Line For Idenmentioning
confidence: 99%
“…In addition, NMR (Wang et al 2014 ) has been shown to be a valuable tool to verify intramolecular hydrogen bonds, which are of prime importance in shielding polarity and in evaluating the effect of N -methylation on conformation. Design, and production of libraries inspired by peptidic natural products such as Sanguinamide A (Nielsen et al 2012 ), Guangomide A and Phepropeptide (Nielsen et al 2014 ; Hewitt et al 2015 ; Schwochert et al 2016 ) have also been demonstrated to be a promising strategy for the identification of permeable peptides and understanding the underlying principles. In particular, recent investigations on cyclic peptides derived from Sanguinamide A resulted in a molecule exhibiting solvent-dependent flexibility and improved permeability (Bockus et al 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…by possessing one important property favourable for development of drugs in bRo5 space. The solubility distribution of the subset suggested that a classification rather than a regression strategy should be applied (Figure 2), and the threshold to distinguish soluble (47) from poorly soluble (18) compounds was fixed at 50 M. This is a slightly more liberal cut-off than that proposed by GSK (30 M) to distinguish compounds having poor from those having intermediate solubility [2].…”
Section: A Solubility Classification Model For a Set Of Structurally mentioning
confidence: 99%